2010
DOI: 10.3148/71.1.2010.33
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Roles, Benefits, and SupportsFor Dietetic Internship Preceptors

Abstract: Evaluation of university-run dietetic internship programs will improve preceptors' experience and, ultimately, increase the capacity for training future dietitians. We attempted to identify preceptors' perceptions of their roles, benefits, and supports, as well as of the skills/traits that students need for internship, and suggested improvements for the internship program. Fifteen of 39 current program preceptors who had supervised more than one intern consented to participate in an ethics-approved research me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…7,8,10,14,16 During the formative research stage, 20 current DI preceptors, 5 nonpreceptors, and 3 internship directors were queried about incentives and obstacles associated with being a preceptor and about interactions with interns. Questions were adapted with author permission from prior surveys that explored similar preceptor issues.…”
Section: Survey Instrument Developmentmentioning
confidence: 99%
“…7,8,10,14,16 During the formative research stage, 20 current DI preceptors, 5 nonpreceptors, and 3 internship directors were queried about incentives and obstacles associated with being a preceptor and about interactions with interns. Questions were adapted with author permission from prior surveys that explored similar preceptor issues.…”
Section: Survey Instrument Developmentmentioning
confidence: 99%
“…CEs provide generalist teaching and pastoral care to students, and support practitioners in their role as preceptors. Preceptors are practitioners who provide direct teaching and education to students during placement and contribute to the evaluation of performance . CEs have been shown to increase workplace capacity in student supervision .…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving physical therapy students and their clinical care output in acute wards also highlight the value of previous clinical practise (Ladyshewsky et al, 1998). Perspectives of clinical educators were explored using surveys, interviews, and/or focus groups in nursing (Barnett et al, 2008), medicine (Sturman et al, 2011), occupational therapy (Rodger et al, 2011), and dietetics (Ortman et al, 2010), which identified that ill-prepared students, paperwork, and time detract from the benefits of having students on placement. Australian data from 97,319 days of supervised medical student placements analyzed across a variety of healthcare domains concur with these findings, indicating that early student placements require increased supervisory time, costs, and resources (Hays, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%